Building trauma-informed research competencies in social work education - Goodwin, Jordan; Tiderington, Emmy (Social work education, 2022)
Trauma exposure is highly prevalent in vulnerable groups served by social workers, as well as in populations that are the focus of social work research. Because of this, the field of social work now recognizes the importance of integrating a trauma-informed framework into clinical practice curricula at the bachelors, masters and doctoral levels. Yet this framework is largely absent from instruction on social work research methods and ethics. Through an assessment of contemporary trauma theory, trauma-informed care, and principles of trauma-informed research, the authors argue for 'universal precautions' with social work research populations and adding a trauma-informed lens to existing guidelines for ethical research with human subjects. Organizational strategies for applying a trauma-informed framework within social work research education include: 1) incorporating trauma awareness into research courses; 2) teaching self-care strategies to combat vicarious traumatization; 3) including explicit content on 'two-way' safety in research courses; 4) providing support for research mentors and teams to encourage trauma-informed supervision; and 5) promoting social work research that rebuilds control and empowerment, such as action research and community-based participatory research.